2018
DOI: 10.1016/j.vaa.2018.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Induction of anesthesia and recovery in donkeys sedated with xylazine: a comparison of midazolam–alfaxalone and midazolam–ketamine

Abstract: Both midazolam-alfaxalone and midazolam-ketamine produced acceptable anesthetic induction and recovery in donkeys after xylazine sedation. Hypoxemia occurred with both treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…However, there was a single case of vomiting with KX that can be related to xylazine being emetic in Hyaenidae and other carnivores (Bufalari et al, 2007; Hahn et al, 2014). The studies on donkeys, captive cougars, Southern river otters, free-ranging African lions, and marmosets had excellent to good scores using ketamine with medetomidine or other drugs such as xylazine (Selmi et al, 2004a; Soto-Azat, Reyes & Medina-Vogel, 2004; Wenger et al, 2010; Bakker et al, 2013; Lescano et al, 2014; Maney et al, 2018). The quality and depth of the anaesthesia were excellent with KM combination providing deep anaesthesia, no body movements or sudden jerks, the absence of pedal and palpebral reflexes, no muscle tone and no response to an external stimulus such as injections and sample collection.…”
Section: Discussionmentioning
confidence: 99%
“…However, there was a single case of vomiting with KX that can be related to xylazine being emetic in Hyaenidae and other carnivores (Bufalari et al, 2007; Hahn et al, 2014). The studies on donkeys, captive cougars, Southern river otters, free-ranging African lions, and marmosets had excellent to good scores using ketamine with medetomidine or other drugs such as xylazine (Selmi et al, 2004a; Soto-Azat, Reyes & Medina-Vogel, 2004; Wenger et al, 2010; Bakker et al, 2013; Lescano et al, 2014; Maney et al, 2018). The quality and depth of the anaesthesia were excellent with KM combination providing deep anaesthesia, no body movements or sudden jerks, the absence of pedal and palpebral reflexes, no muscle tone and no response to an external stimulus such as injections and sample collection.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study compared midazolam (0.05 mg/kg IV) and alfaxalone (1 mg/kg IV) with midazolam (0.05 mg/kg IV) and ketamine (2.2 mg/kg IV) following premedication with xylazine (2 mg/kg IM, followed by 0.5 mg/kg IV after 60 minutes) in donkeys. 29 Inductions were quicker with alfaxalone but recoveries were smoother and shorter in the ketamine group. Hypoxemia occurred with both drug combinations.…”
Section: Alfaxalonementioning
confidence: 95%
“…15 The amount of research is sparse, but it has been shown that these species develop hypoxaemia under general anaesthesia similarly to the horse. [16][17][18][19] However, mules exist in a wide variety of weights and body shapes, which may lead to large variations in the development of hypoxaemia. 15 Perianaesthetic hypoxaemia is a common issue with equine patients, and treatment options are not always efficient.…”
Section: Hypoxaemiamentioning
confidence: 99%
“…Besides differences in drug requirements, no major relevant anatomical or physiological differences in pulmonary function are expected between horses, donkeys and mules 15 . The amount of research is sparse, but it has been shown that these species develop hypoxaemia under general anaesthesia similarly to the horse 16–19 . However, mules exist in a wide variety of weights and body shapes, which may lead to large variations in the development of hypoxaemia 15…”
Section: Introductionmentioning
confidence: 99%